Soil respiration and organic carbon changes along a chronosequence of Pinus nigra forest stands - Aydın, Miraç; Rages, Ashraf Anwar (BioResources, 2024)
Understanding the trajectory of changes in soil respiration (Rs) and soil organic carbon (SOC) with stand ages of the black pine (Pinus nigra Arnold) forest is essential for forest management and carbon budget estimates. In this research, changes of Rs and SOC were studied with respect to stand age in a chronosequence of three age classes of P. nigra plantations consisting of young (0 to 10-year-olds), middle-aged (11- to 20-year-olds), and pre-mature (35- to 45-year-olds) forest stands. Rs rates, soil temperature, and soil moisture were measured using an automated dynamic survey chamber (Li-8100A) for a year, encompassing summer, fall, winter, and spring seasons. Mean Rs significantly increased from young- to middle-aged and then stabilized, with effluxes ranging from 2.46 to 2.94 µmol CO2 m-2 s-1. Forest litter significantly increased with stand age, but not the SOC in the mineral soil layers. The Rs showed a positive correlation with soil temperature (0.77) and air temperature (0.75) but not with soil moisture (-0.43). The present results highlight the importance of stand age in assessing carbon budget and provide essential information for forest managers and stakeholders in evaluating the potential of P. nigra forests as tools for carbon sequestration and mitigating global warming impacts.
Keywords: soil temperature; dynamic chamber; stand age; co2 emissions; black pine; soil moisture; TP248.13-248.65; Biotechnology; 15. Life on land; 13. Climate action